Challenges Faced by Generation Z Learners in Using Video Tasks to Enhance English Speaking Skills through the TPACK Approach - Jati, Anida Fadhilah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this study is to explore the challenges faced by Generation Z students in utilizing video-based tasks to enhance their English-Speaking skills through the Technological Pedagogical Content Knowledge (TPACK) framework. Generation Z, born between 1997 and 2012, has grown up surrounded by digital technology, which makes them highly familiar with digital tools but also presents challenges when traditional teaching methods fail to align with their tech-driven learning preferences. This study aims to identify the barriers these students encounter when using video-based tasks in language learning, particularly in terms of technology, pedagogy, and content integration. The research was conducted with 30 English Literature students at a private university in Bekasi, Indonesia. A narrative inquiry methodology was used, involving semi-structured interviews, observations, and document analysis, which were analyzed thematically using a multiple case study approach. The findings reveal key challenges such as limited access to technology, time management difficulties, and psychological barriers like embarrassment or lack of confidence when speaking on camera. Despite these challenges, the study highlights that, with appropriate support and integration of the TPACK framework, video-based tasks significantly improve students' speaking proficiency and creativity. This research underscores the importance of considering both technological and psychological factors to optimize language learning experiences for Generation Z students.